A study on the impact of campaign finance, political capital and gender on electoral performance - Speck,Bruno Wilhelm (2014)
This article analyzes the association between political finance and electoral performance in the 2010 Brazilian elections for state and federal deputies. It also investigates the interaction effect of incumbency and gender on this association. We conclude: (i) there is a positive and statistically significant association between political finance and electoral performance, yet the intensity of this association varies according to the type of candidate; (ii) the association is stronger for challengers than for incumbents - thus extending the "Jacobson effect" to the Brazilian case; and (iii) the association is stronger for women than for men - which suggests an extension of the idea underlying the "Jacobson effect". The association between finance and electoral performance tends to be stronger for candidates facing electoral disadvantages, whether these stem from limited political capital, gender discrimination, or any other factor not studied here resulting in a similar effect. Political finance works as a tool that, to some extent, may counteract the negative effect of such factors on electoral performance.